Usefulness of four-limb blood pressure measurement in prediction of overall and cardiovascular mortality in acute myocardial infarction - Hsu, Po-Chao (Int J Med Sci, 2020)
Four-limb blood pressure measurement could improve mortality prediction in the elderly. However, there was no study to evaluate whether such measurement was still useful in predicting overall and cardiovascular (CV) mortality in acute myocardial infarction (AMI). Two hundred AMI patients admitted to cardiac care unit were enrolled. The 4-limb blood pressures, inter-limb blood pressure differences, and ankle brachial index (ABI) were measured using an ABI-form device. The median follow-up to mortality was 64 months (25th-75th percentile: 5-174 months). There were 40 and 138 patients documented as CV and overall mortality, respectively. After multivariable adjustment, the ankle diastolic blood pressure (DBP) on the lower side, ABI value, ABI < 0.9, interarm DBP difference, interankle systolic blood pressure (SBP) and DBP differences, interankle SBP difference ≥ 15 mmHg, and interankle DBP difference ≥ 10 mmHg could predict overall mortality (P ≤ 0.025). The ankle DBP on the lower side, interankle DBP difference, and interankle DBP difference ≥ 10 mmHg could predict CV mortality (P ≤ 0.031). In addition, in the Nested Cox model, the model including the ankle DBP on the lower side and the model including interankle DBP difference had the best value for overall and CV mortality prediction, respectively (P ≤ 0.031). In AMI patients, 4-limb blood pressure measurement could generate several useful parameters in predicting overall and CV mortality. Furthermore, ankle DBP on the lower side and interankle DBP difference were the most powerful parameters in prediction of overall and CV mortality, respectively.